International commercial arbitration law, procedures, and facilities in India \ - Singhania & Co; Singhania & Co. (New Delhi, India : Singhania, 1985)
With reference to the Indian Arbitration Act, 1940; includes documents.
Keywords: Arbitration and award -- India; International commercial arbitration